CONTINUITY OF TEACHING STUDENTS IN HIGHER EDUCATION INSTITUTIONS ON THE BASIS OF MODERN APPROACHES (Academicia Globe: Inderscience Research, 2022)
This article highlights the importance of teaching students in higher education using modern pedagogical technologies. Ways to improve the quality of education based on modern approaches are described.